2018
DOI: 10.1080/10790268.2018.1544878
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic spinal cord injury in West Virginia: Disparities by insurance and discharge disposition from an acute care hospital

Abstract: Context: Medicaid has been linked to worse outcomes in a variety of diagnoses such as lung cancer, uterine cancer, and cardiac valve procedures. It has furthermore been linked to the reduced health-related quality of life outcomes after traumatic injuries when compared to other insurance groups. In spinal cord injury (SCI), the care provided in the subacute setting may vary based upon payor status, which may have implications on outcomes and cost of care. Design: A retrospective review utilizing the institutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 12 publications
2
10
0
Order By: Relevance
“…Our previous work on this patient population indicated that patients with private insurance are more likely to be discharged to an acute rehabilitation center and thus more apt to receive the intense therapy required to maximize recovery. [7] These results are similar to other investigations related to insurance coverage for people with SCI. For example, Tate et al found people with Medicaid coverage received less benefits than those covered by other insurance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our previous work on this patient population indicated that patients with private insurance are more likely to be discharged to an acute rehabilitation center and thus more apt to receive the intense therapy required to maximize recovery. [7] These results are similar to other investigations related to insurance coverage for people with SCI. For example, Tate et al found people with Medicaid coverage received less benefits than those covered by other insurance.…”
Section: Discussionsupporting
confidence: 90%
“…[5,6] Our previous research indicated that people with SCI in West Virginia who have publicly funded Medicaid insurance have longer hospital stays and are more apt to be discharged home or to a skilled nursing facility rather than a specialized rehabilitation facility. [7] This disparity in discharge disposition likely results from inpatient rehabilitation facility admission being a "non-covered service" as per the West Virginia Health and Human Resources Bureau of Medical Services [8] and may lead to patients with Medicaid being released to a setting that lacks specially designed SCI programs such as a private home or nursing home. Lack of specialized care may prevent patients from reaching optimum function, independence, and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…[32,33] Fewer studies have specifically reported on the role of insurance status relative to health care outcomes. [34] Specifically, while several studies have investigated the role of insurance status among patients undergoing HP surgery, these reports have largely focused on differences in perioperative outcomes among patients already admitted to a certain type of hospital (e.g. urban, teaching, not-for-profit, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Also in this issue, outcomes research from Switzerland identifies transportation as a major factor in access to care, 10 and in the U.S., a West Virginia study shows that type of insurance is a factor in length of stay, cost of care, and discharge disposition. 11 Efforts to track the long-term adjustment of individuals with spinal cord injury extends to the impact of long-term care on their caregivers, 12 a relative recent avenue of research.…”
Section: Care and Research For Spinal Cord Injury: A Changing Landscapementioning
confidence: 99%